The Effect Of Non-Financial Performance On Managerial Performance Mediated By The Clarity Of Role And Procedural Justice - Setiawati, Erma; Bawono, Andy Dwi Bayu; Nurhidayati, Diyah (Universitas Muhammadiyah Surakarta, 2021)
The study aims to test the influence of non-financial and managerial performance with the clarity of role and procedural justice as the mediation variables. This quantitative study used a descriptive approach. The population in this study was sharia bank employees in Surakarta, Indonesia. The sampling technique employed in this study was convenience sampling. The sample criteria in this study consisted of the respondents who had subordinate employees under and had worked at least a year; as for the samples in this study, it amounted to 126 respondents. The data used in the study was the primary data, collected through surveys in physical form. The data analysis then utilized multiple linear regression and moderating regression with an absolute value-difference approach. The study results with multiple linear regression analyses showed that non-financial performance influenced managerial performance, the clarity of the role affected the managerial performance, procedural justice influenced managerial performance, and non-financial performance affected the managerial performance, with the clarity of role mediation. However, the procedural justice variables did not mediate the influence of non-financial performance on managerial performance.